BIG BOOK OF TRANSPORTATION - Megawati, Fika; Setyowati, Nafi'ah Aghni (ELite Journal : International Journal of Education, Language and Literature, 2023)
Big Book is a media product designed to enhance shared reading experiences between teachers and students, particularly in English language learning. It features unique illustrations, repeated vocabulary, familiar storylines, and simple grammar patterns. This resource promotes interactive and engaging learning, helping students grasp content through clear and vivid pictures. Its accessible design allows for easy assembly using basic materials such as pencils, drawing books, markers, crayons, and binder clips, making it cost-effective and adaptable. This product encourages group learning activities and fosters new learning habits while enhancing students’ motivation, confidence, and enjoyment in language acquisition. Besides, teachers and students can explore imaginative and innovative educational resources through this media. The Big Book entitled “Transportation on land, air, and sea” consists of 10 pages, each focusing on a different transportation category. By simplifying complex concepts and creating an interactive environment, the Big Book helps students identify words in their surroundings and strengthens their understanding of story content. The advantages of using the Big Book include increased motivation, confidence, ease, pleasure in learning, and the formation of new learning habits. Overall, the Big Book is useful for identifying words in the environment and supporting group learning activities